Trigona Honey Bee Cultivation as a Sustainable Agricultural Alternative in Bandarsari Village, Padangratu District, Central Lampung Regency - Arifiyanto, Achmad; Nukmal, Nismah; Pratami, Gina Dania; Lestari, Elly Rustiati (Talenta Publisher, 2022)
Padangratu District, Central Lampung Regency, is home to Bandarsari Village. The majority of the population works as farmers, mostly in oil palm plantations, rubber plantations, and rice fields. This village's location is ideal for the growth of honey bee agriculture. This service activity seeks to assist in the development of Trigona honey bee farming training as an alternative approach to sustainable agriculture. Residents were instructed in the production of Trigona honey bee growing techniques using lecture methods and field coaching. This is an ideal environment for the production of Trigona honey bees, since it is supported by plentiful natural resources such as fruit trees, plantations, and flowers. This activity is projected to produce information on Trigona honey bee culture and its benefits, knowledge of different forms of natural honey bee feed, and video lessons on Trigona honey bee cultivation. The outputs of Trigona honey bee farming are not just economically valuable. Bees' ecological role will also aid to preserve the plantation ecology and pollinate the fruit and flowers of the inhabitants. Trigona honey products are also advantageous as a source of living pharmacy that generates money. The most significant aspect is that the Trigona bee is stingless, making it safe for inhabitants and simple to care for.